Miokarda perfūzijas scintigrāfija SPECT/CT - Pavlova, Sandra (Latvijas Universitāte, 2012)
Miokarda perfūzijas skenēšana ir kodolmedicīnas procedūra, kas dod informāciju par sirds muskuļa stāvokli. Radiologa asistenta darbs veicot šo izmeklējumu ietver vairākus posmus un katrā no tiem radiologa asistentam ir cits uzdevums. Kodolmedicīnā, lai optimizētu pacientu dozas un lai nodrošinātu atbilstošu attēla kvalitāti, ir nepieciešama visa attēlošanas procesa rūpīga optimizācija un visu iekārtu sistemātiska darbības kvalitātes pārbaude. Izmeklējuma optimizācija kodolmedicīnā ietver izmeklējumam atbilstoša izotopa un tā dozas sagatavošanu, kā arī atbilstošu attēlošanas metodikas parametru izvēli. Starptautiskās rekomendācijas norāda, ka operatoram ir jānodrošina, lai dozu standartlīmeņi diagnostikā tiktu noteikti un regulāri tiktu pārskatīti, lai sekotu līdzi tehnoloģijas uzlabojumiem, un, šajās darbībās kā vadlīnijas ir jāizmanto PDS – drošības pamatstandarts (angl.BSS - Basic Safety Standarts) un kodolmedicīnā vadošie standarti. Darbā tika analizēta pacientu un medicīnas personāla aizsardzības pamatprincipi. Pacientam pirms izmeklējuma ir jāsaņem plaša informācija par izmeklējuma norisi un jābūt pāliecinātam, ka saņems labākās iespējamās kvalitātes medicīnisko pakalpojumu. Tāpēc profesionāļiem, atbildīgiem par pacienta aprūpi ir jānodrošina augstākās kvalitātes izmeklējuma sniegšanu. Darba gaitā apstiprināju izvirzīto hipotēzi, ka radiologa asistenta darba kvalitātei MPS izmeklējuma veikšanas procesā ir izšķiroša nozīme

The title of the is ,,Myocardial Perfusion Imaging SPECT/CT”. It consists of three parts – literature review, investigation and conclusions. There were analysed the available literature on myocardial perfusion SPECT/CT in the first part. Myocardial perfusion imaging is nuclear medicine procedure assessing myocardial viability. Nuclear medicine technologist must ensure each examination is performed correctly that guarentees the quality of the results. Scanning includes several steps and technologist is involved in each of them. Myocardial perfusion imaging with pharmacological stress testing in a an accepted technique in nuclear medicine. A routine quality control programme for SPECT/CT gamma cameras should incluse specific SPECT/CT quality controls. This enables to reduce patient doses as well as improve quality of images. International Regulations recommend that technologist are responsible for checking the dose standard levels in nuclear medicine regularly. In addition, any technical improvements in this field must be followed and introduced in this examination, and BSS( Basic Safety Standarts) and general standarts in nuclear medicine must be used as guidelines for quality control in MRI. Technologists must provide patients with simple and clear information concerning the procedure and prepare the right dose of radiopharmaceuticals. This is followed by instructing patients their behavior prior to and after the injection. Study protocols must be filled in correctly and precisely. Patients appropriate positioning is extremely relevant. It ensures patient comfort and quality of images. The aim of the thesis was to investigate the positioning of patients, injection procedure, preparing radiopharmaceuticals, the quality control of the camera as well as the filling in the study protocol. During the process of investigating the subject, the author came to conclusion that technologist play an important an essential role in MRI SPECT/CT which came not be underestimated. His professional expertise is vital for safeguarding patient’s well being, maintaining an operating procedure and providing the high quality of outcome
Myocardial perfusion SPECT/CT
Keywords: Medicīna